Where Bulletin and Transactions can be Consulted (95510b19-63ae-4cbb-a7b4-2a3a06decdec) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
ARIZONA Tucson University of AriZona, Mining Engineering Society. B CALIFORNIA Berkeley University of California, Mining Asso. B University of California, Library. B & T Los Angeles Chamber of Mines and Oil. B Southern California Local Section. T Public Library. B & T Oakland Oakland Free Library. T San Francisco California State Mining Bureau. T Mechanic's Merchantile Library. B Mining and Scientific Press. B Stanford University Stanford University Geological and Mining Society. B San Diego Public Library. B COLORADO Boulder University of Colorado, Library. T Denver Bureau of Mines. B Colorado Scientific Society. B Mining American. B Denver Public Library. B & T Golden Colorado School of Mines Magazine. B Colorado School of Mines Library. T Colorado School of Mines Scientific Society. B